Centro de educación especial e integración laboral para personas con discapacidades - escala zona 6704.00 m2 aproximadamente - Villalva Guzmán, Ana María (2015)
“… To work each within their sphere of competence and according to their possibilities, for a more human dwelling and city, for a city that is architecturally capable and ordered so that every man, even those that use a wheelchair, can circulate, access fully unimpeded, freely…” (Le Corbusier, s.f.) The project is located lower montane, in the parish of Turubamba south of Quito, in an environment with a privileged setting in view of the Atacazo and Pichincha mountains, but in an area where urban sprawl has spread in an uncontrolled way which shows a lack of architectural planning, services, facilities, landscape and environmental attributes, and a high incidence of people with disabilities but a shortage of places to attend them. A center of special education and occupational integration is proposed, which emphasizes on the concept of equal opportunities, because barriers for social inclusion are not only from the physical space but also from people’s attitude toward impairment. When providing an inclusive space, with universal design, quality public space, environmental consciousness, among others, social cohesion can be achieved and quality of life will improve for these people. People of 15 years of age and older will have the education and capacitation needed to be incorporated on an occupational aspect of life therefore enhancing their inclusion in society and their own personal development. Spaces created will vary materiality, color, texture, sounds, temperature and form, so that people with sensory, physical or intellectual impairment can read the space around them easily and their experience within it improves their learning performance.